The Role of PEMUDATA in Islamic Education: A Case Study of Subulussalam City - Nawawi, Nawawi; Hanum, Azizah; Arsyad, Junaidi (Journal of Social Work and Science Education, 2025)
This study examines the role of the Persatuan Mubaligh Muda Sada Kata (PEMUDATA) as a youth missionary association in the development of non-formal Islamic education in the city of Subulussalam. Using a qualitative approach with a case study method, data was collected through in-depth interviews, participatory observation, and documentation of the activities carried out by the organization. The results of the study indicate that PEMUDATA has made a significant contribution to expanding access to Islamic education through its da’wah programs, religious training, and youth development initiatives at mosques. The uniqueness of this organization lies in its adaptive approach to the local socio-cultural context and the ability of its members to build intergenerational communication. The practical implications of these findings suggest that youth missionary associations like PEMUDATA can be strategic partners for local governments and Islamic educational institutions in improving religious literacy among the community, especially in areas not fully reached by formal education. This research contributes to the literature on non-formal Islamic education and opens opportunities for developing partnership models between the state, society, and youth religious organizations at the local level.